Assessment Center Evaluation in Indonesia: An Exploratory Study - Lovihan, Mike A. K.; Handoyo, Seger; Mastuti, Endah; Nachtwei, Jens (RSF Conference Series: Business, Management and Social Sciences, 2024)
Although assessment center practice continues to spread to Asian countries, no published study exists that evaluates the quality of AC within the largest populous country of Indonesia. Therefore, this study aims to determine the quality of assessment center methodology in Indonesia. Then, the result is compared to a prior benchmarking of the BACDi-instrument. The results indicate no differences between Indonesian and German assessment centers' overall development and post-processing quality phases. The difference between Indonesian and German assessment centers was found in conduction quality. The assessment center practice has to consider the context of other aspects that could lead to its methodology improvement in future practice. This study is the first detailed and standardized representation of assessment center methodology quality that adequately explains every phase within the assessment center in Indonesia, and more widely, is discussed.